Serum And Bone Marrow Prostatic Spe iafic Antigen And Pliostatic Acid PbQs:pbatase Levels In Patient's With Prostatic Caueer - Hussein, Z. M.; Salman, M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Serum and hone marrow levels 0f ptostatic specific antigen a!ld prostaticacid   phosphatase were-   analyzed   n .d q !antUIÂ·ed  by    Glottble     antibody.raqioimrrumoa,ssay in 3.6 _prosÂ·tatic cance-r , patietll$inc!udlng 2'3 with metaStaticc:anc.et.  There  was :a  sÂ·i.gnÂ·ifl.co.m  cotneJaÂ·,ion   betwÂ¢enÂ·   th.e 'Setl;liD   a,n,d  bopemat::tow: levels  of JlrostaticÂ· Â·s, pecific antigen and prqstati'c  acid  pho phata.Sejndependently of the m.et ta:st;s (p< .QO: O 1 ).. Np pÂ·ath;nt Â·willprqsta,ticancer:and  posiriY:e bohe  .matrW   pros.tatJc      spec:ifk  .an.tif?;en    or  p_rostati        acid pbos:pbatase l vels lla:d  QQnnaÂ·l  serum level$. Qwintl'fication  of  bone: marrow: ptostatit specific antigen and .prostati-c acid phosp'ha't s"'dees.Jlot prov,id'e 1');1Qre infgrmationÂ· thah. does s rum  deterritination.